Rerajahan Sebagai Sumber Inspirasi Penciptaan Seni Lukis - Arsad Tri Gunawan, I Made; Wirakesuma , I Nengah; Setem, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2022)
Departing from an idea about rerajahan illustration which always has its own meaning in each of its strange forms, it creates an impetus to present rerajahan visualization by combining certain techniques and references to achieve goals and meanings that are in accordance with what is desired. The problem faced is how to process the rerajahan visuals to represent ideas so that the embodiment of the work looks interesting. The purpose and benefits are to provide a new reflection and elevate the existence of rerajahan which is full of use in various yadnya ceremonies in Bali, and to increase the author's understanding of the forms of rerajahan. To answer what is the purpose of this work, the method of creation uses exploration, improvisation, and forming. By arranging elements of art, and going through the stages of exploration, improvisation, and the forming stage, and combined with ideas and ideas to create 6 works entitled: 1)